Differentiation Rules: Learn It 2

The Basic Rules Cont.

The Sum, Difference, and Constant Multiple Rules

We find our next differentiation rules by looking at derivatives of sums, differences, and constant multiples of functions. Just as when we work with functions, there are rules that make it easier to find derivatives of functions that we add, subtract, or multiply by a constant. 

sum, difference, and constant multiple rules

Let [latex]f(x)[/latex] and [latex]g(x)[/latex] be differentiable functions and [latex]k[/latex] be a constant. Then each of the following equations holds.

 

Sum Rule: The derivative of the sum of a function [latex]f[/latex] and a function [latex]g[/latex] is the same as the sum of the derivative of [latex]f[/latex] and the derivative of [latex]g[/latex].

[latex]\frac{d}{dx}(f(x)+g(x))=\frac{d}{dx}(f(x))+\frac{d}{dx}(g(x))[/latex];

that is,

for [latex]j(x)=f(x)+g(x), \, j^{\prime}(x)=f^{\prime}(x)+g^{\prime}(x)[/latex]
 

Difference Rule: The derivative of the difference of a function [latex]f[/latex] and a function [latex]g[/latex] is the same as the difference of the derivative of [latex]f[/latex] and the derivative of [latex]g[/latex].

[latex]\frac{d}{dx}(f(x)-g(x))=\frac{d}{dx}(f(x))-\frac{d}{dx}(g(x))[/latex];
 

that is,

for [latex]j(x)=f(x)-g(x), \, j^{\prime}(x)=f^{\prime}(x)-g^{\prime}(x)[/latex]
 

Constant Multiple Rule: The derivative of a constant [latex]k[/latex] multiplied by a function [latex]f[/latex] is the same as the constant multiplied by the derivative:

[latex]\frac{d}{dx}(kf(x))=k\frac{d}{dx}(f(x))[/latex];

that is,

for [latex]j(x)=kf(x), \, j^{\prime}(x)=kf^{\prime}(x)[/latex]

Proof


We provide only the proof of the sum rule here. The rest follow in a similar manner.

For differentiable functions [latex]f(x)[/latex] and [latex]g(x)[/latex], we set [latex]j(x)=f(x)+g(x)[/latex]. Using the limit definition of the derivative we have

[latex]j^{\prime}(x)=\underset{h\to 0}{\lim}\dfrac{j(x+h)-j(x)}{h}[/latex]

By substituting [latex]j(x+h)=f(x+h)+g(x+h)[/latex] and [latex]j(x)=f(x)+g(x)[/latex], we obtain

[latex]j^{\prime}(x)=\underset{h\to 0}{\lim}\dfrac{(f(x+h)+g(x+h))-(f(x)+g(x))}{h}[/latex]

Rearranging and regrouping the terms, we have

[latex]j^{\prime}(x)=\underset{h\to 0}{\lim}(\frac{f(x+h)-f(x)}{h}+\frac{g(x+h)-g(x)}{h})[/latex]

We now apply the sum law for limits and the definition of the derivative to obtain

[latex]j^{\prime}(x)=\underset{h\to 0}{\lim}(\frac{f(x+h)-f(x)}{h})+\underset{h\to 0}{\lim}(\frac{g(x+h)-g(x)}{h})=f^{\prime}(x)+g^{\prime}(x)[/latex]

[latex]_\blacksquare[/latex]

Find the derivative of [latex]g(x)=3x^2[/latex] and compare it to the derivative of [latex]f(x)=x^2[/latex].

Find the derivative of [latex]f(x)=2x^5+7[/latex].

Find the equation of the line tangent to the graph of [latex]f(x)=x^2-4x+6[/latex] at [latex]x=1[/latex].